2002
DOI: 10.1139/f02-067
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-based habitat compression in the Neuse River Estuary: context-dependent shifts in behavioral avoidance thresholds

Abstract: Anthropogenic activities in estuarine watersheds alter physical and chemical characteristics of these ecosystems. Increased nutrient loading and changes in hydrology affect oxygen budgets and subsequently alter the spatial and temporal extent of hypoxia. We used classification and regression tree analyses to examine behavioral avoidance thresholds over a range of dissolved oxygen concentrations. In an examination of 10 fish species, all avoided areas with dissolved oxygen concentrations of <2.0 mg·L–1. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
240
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(258 citation statements)
references
References 33 publications
14
240
3
1
Order By: Relevance
“…Further work with telemetry in areas that bottlenose dolphins frequent may help determine how subadult red drum balance feeding and predation risk (Gilliam & Fraser 1987). The response of organisms to estuarine water quality variables can be complex (Eby & Crowder 2002, Bell et al 2003. In the present study, there was a positive relationship between age-2 red drum and temperature, but only in the Neuse River and Outer Banks regions.…”
Section: Habitat Use Of Red Drummentioning
confidence: 47%
See 1 more Smart Citation
“…Further work with telemetry in areas that bottlenose dolphins frequent may help determine how subadult red drum balance feeding and predation risk (Gilliam & Fraser 1987). The response of organisms to estuarine water quality variables can be complex (Eby & Crowder 2002, Bell et al 2003. In the present study, there was a positive relationship between age-2 red drum and temperature, but only in the Neuse River and Outer Banks regions.…”
Section: Habitat Use Of Red Drummentioning
confidence: 47%
“…areas with dissolved oxygen concentration < 2 mg l -1 ) on fishes are well docu- mented, often resulting in behavioral avoidance or reduced growth or survival (Pihl et al 1991, Eby & Crowder 2002). We did not observe significant effects of dissolved oxygen concentration on the distribution of either age class of red drum from the gill net survey, but subadult red drum CPUE was positively related to dissolved oxygen levels in Hancock Creek.…”
Section: Habitat Use Of Red Drummentioning
confidence: 99%
“…To maintain a healthy aquatic life, the daily minimum DO requirement claimed to be 5 mg/L in the water column (NDDoH, 2010); however, amount of DO needed to prevent mortality differs among species and between life stages. For instance, fish eggs and young fish, are more sensitive to low DO than adults (Eby and Crowder, 2002;Ludsin et al, 2009). Hypoxia (i.e., DO <2 mg L −1 ) can affect biological communities in the aquatic ecosystem; for instance, prolonged low DO levels can cause fish kills (Rao et al, 2014) and benthic macroinvertebrate kill (Bridgeman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Given the interdisciplinary nature of the phenomenon, marine hypoxia has generated a widespread interest among scientists in different disciplines (for example, see Eby and Crowder (2002);Breitburg (2002); Borsuk et al, (2004); Taylor and Eggleston (2004)). Scientific studies have found evidence that hypoxia can affect different fish species in various ways such growth and mortality (for example, Peterson et al, 2000;Miller et al, 2002;Stierhoff et al, 2009;Thomas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%